Annual report on regional progress and challenges in relation to the 2030 Agenda for Sustainable Development in Latin America and the Caribbean (UN ECLAC SantiagoCL, 2017)
Offers a brief analysis of the regional and global context in which the countries of the region will be pursuing the SDGs in the coming years. Deals with specific challenges to the effective implementation of the 2030 Agenda and the sustainable development goals. Describes and analyses the different institutional mechanisms and the norms and instruments developed in the different countries to promote the goals.Intends to identify the starting point and the bases on which the work begins.
Documentation Centre has: 2017-'18